(untitled) (Journal of the College of Education for Women, 2019)
The Aim of this study is to identify the importance of associations and professional associations in the field of libraries and information at the global level and at the Arab level through analytical study carried out by the researcher adopted the security of the international federation of libraries IFLA model at the global level, associations, Egyptian information and libraries in the Arab world and the imposition study a number of recommendations. Most important to increase funding for unions and professional associations, and the need to establish sessions and meet with the owners of the profession in order to exchange experiences and skills development.